Psychological skills of elite age-group swimmers
Elite age-group swimmers were found to have significantly advanced psychological skill development when compared to their sub-elite counterparts. When compared topelite international level swimmers, elite age-groupers were more susceptible to the negative effects of precompetition anxiety. These results suggest that age-group swimmers would benefit from a psychological skills training program.